Critical Literacy in Indonesian Language Learning in Higher Education - Yulian Dinihari; Endang Wiyanti; Zetty Karyati; Retna Ningsih; Anggun Citra Dini Dwi Puspitasari (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe students' critical literacy skills in Indonesian language learning at university. The study was conducted at Indraprasta PGRI University, Jakarta, in the even semester of the 2025/2026 academic year. The study population consisted of 120 students taking Indonesian language courses, while the sample consisted of 35 students selected using a purposive sampling technique. The study employed a descriptive quantitative approach. The research instrument was a critical literacy questionnaire covering indicators of text analysis, argumentation evaluation, social interpretation, critical reflection, and opinion formation. Data analysis was conducted using descriptive statistics in the form of percentages to determine the level of students' critical literacy skills. The results showed that students' critical literacy skills were in the good category with an average percentage of 81.8%. The social interpretation indicator achieved the highest percentage at 85%, while the argumentation evaluation indicator achieved the lowest percentage at 78%. Furthermore, learning activities based on critical discussion, text analysis, and learning reflection showed a relationship with the development of students' critical literacy skills. The results of this study indicate that Indonesian language learning at university plays a crucial role in developing students' critical thinking skills in the digital era.